FAKTOR YANG MEMPENGARUHI KEPUASAN WISATAWAN MANCANEGARA MENGGUNAKAN KAPAL PESIAR PINISI PRANA DI LABUAN BAJO - Hidayatullah, Syarif; Kusuma Negara, I Made; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p18, 2023)
As one of the National Tourism Strategic Areas, Labuan Bajo is starting to be visited by many tourists. Many pinisi ships operate in Labuan Bajo. One of them is Prana. Due to the high price offered, the Prana manager must give satisfaction to tourists. This journal aims to determine the characteristics of tourists and the factors that influence the satisfaction of tourists who use the pinisi Prana cruise ship in Labuan Bajo. The sample choosen with a purposive sampling technique with a number of respondents 100 foreign tourists. Data analysis techniques: validity test, reliability test, and factor analysis. The results indicate that: the characteristics of tourists who use the pinisi Prana cruise ship in Labuan Bajo are 25 - 50 years old, male, work as an entrepreneur, latest undergraduate education, not married, for recreation, stay for 5-7 days, get information from friends / relatives, going on trips with friends, and planning trips by yourself. From 2 initial factors consisting of 22 indicators, 6 factors are formed that affect the satisfaction of tourists who use the pinisi Prana cruise ship. The 6 factors are service quality (29,20%), security (8,61%), price & image (7,81%), convenience (6,11%), facilities (5,33%), and trust (5,07%). The dominant factor affecting the satisfaction of tourists using the Pinisi Prana cruise ship in Labuan Bajo is the quality of service with an eigenvalue of 6,42 and a percentage of variance of 29,20%.